Synopsis of the genus Pharaonus (Coleoptera: Scarabaeidae: Rutelinae), with descriptions of new taxa - Keith, Denis; Sabatinelli, Guido; Uliana, Marco (Zootaxa, 2015)
An overview of the genus Pharaonus Blanchard, 1851 is presented. Pharaonus farsensis new species and P. adelphus new species are described from Iran, P. lederi turcmenius Ohaus, 1941 is recognized as new synonym of P. lederi (Reitter, 1888), and the subgenus Tamerlanius new subgenus is proposed for the two central-Asian species. New distribution records and systematic notes are presented: P. caucasicus (Reitter, 1888) is removed from the fauna of Iran and P. varicoloreus (Burmeister, 1844) from that of Israel; P. fasciculatus (Burmeister, 1844) is reported for the first time from Israel, P. semenowi (Reitter, 1888) from Tajikistan. All known species are illustrated and a key to species is presented.